What makes a balanced leader?: an Islamic perspective - Abdelrahman Farrag, Dalia; Abdelzaher, Dina; Mohamed, Ahmed Amin; Mohamed, Ahmed Amin; Baykal, Elif; Darrag, Menatallah; El Odessy, Dina; El-Bassiouny, Noha; El-Bassiouny, Noha; El-Sherbiny, Youmna; ElKaleh, Eman S.; Farrag, Noha; et al. (Management, Spirituality and Religion, 2023)
Despite continuous public interest in leadership studies as well as the abundance of extant literature, the world continues to face leadership predicaments. Given the global crises mankind has been recently exposed to, which include the financial crisis of 2008 as well as the COVID-19 pandemic, further exploration of leadership concepts seems warranted. This edited book aims at introducing the concept of Balanced Leadership from an Islamic perspective. Drawing on both leadership and Islamic studies, the book synchronizes between secular and religious knowledge domains whilst introducing the notion of balance to mainstream leadership literature. The conceptualizations presented in the book serve to dissect the leadership literature, present historical and philosophical accounts of the balanced leadership concept and infuse that with Islamic theology. The book is useful for practitioners interested in leadership studies as well as scholars and researchers aiming at extending the leadership literature